INTEGRAL ASSESSMENT OF THE SEVERITY OF THE CONDITION AND PREDICTION OF OUTCOMES OF CHILDREN WITH CRITICAL CONDITIONS (Herald of the National Children's Medical Center, 2022)
This article is devoted to the issues of integral assessment of the condition and predicting the outcomes of childrenwith critical conditions at the prehospital stage of emergency medical care. Data from the case histories of 895 children wereretrospectively studied and 143 children aged 12 to 18 years old were selected from them, who were in the ICU of the TashPMIclinic with somatic pathology and the presence of insufVciency in the function of vital organs, who were admitted through96 the ambulance of the city of Tashkent. A comparative analysis of the statistical parameters of the MODS variable scale wascarried out to determine the diagnostic efciency. It has been established that the MODS patient condition severity scale canbe used in patients with critical conditions, both for individual prognosis of the outcome of the disease, and in assessing theeffectiveness of intensive care at the stages of treatment. The use of scoring only the respiratory, cardiovascular and renalsystems on the MODS scale can nd practical application in assessing individual outcome prognosis in critically ill patients.
Keywords: critical states; scale; assessment of the state; integral assessment; variables of integral scales; outcome; forecasting